2011
DOI: 10.1111/j.1525-139x.2011.00924.x
|View full text |Cite
|
Sign up to set email alerts
|

The Current State of Interventional Nephrology in India

Abstract: Nephrologists in India have embraced providing complete care to their patients and recognize the benefits of coordinated care. This review describes the practice of interventional nephrology in India. Even though the benefits of using tunneled catheters over nontunneled catheters are well recognized, the use of nontunneled catheters is preferred, primarily because of financial constraints and the lack of training facilities. Arteriovenous fistulas (AVFs) are the most common form of dialysis vascular access, of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…2 Over the years, some nephrologists from around the world, particularly from Europe (Italy and Germany), India and now United States, have started creating the AVF. [3][4][5][6][7][8][9] Reported outcomes of AVFs created by nephrologists are similar to that of the surgeons. 9 A survey done in Italy showed that about 50% of nephrologists in the country perform AVF surgery.…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…2 Over the years, some nephrologists from around the world, particularly from Europe (Italy and Germany), India and now United States, have started creating the AVF. [3][4][5][6][7][8][9] Reported outcomes of AVFs created by nephrologists are similar to that of the surgeons. 9 A survey done in Italy showed that about 50% of nephrologists in the country perform AVF surgery.…”
Section: Introductionmentioning
confidence: 77%
“…The study reported no difference in the outcome of AVFs created by the nephrologists and surgeons. 6 In our study 166 AVFs were created by a single nephrologist over a 3-year period. 78(47%) were radiocephalic, 76(45.7%) were brachiocephalic and 12(7.3%) were brachiobasilic AVFs.…”
Section: Discussionmentioning
confidence: 99%
“…Other authors have published experiences on the role of interventional nephrologists regarding vascular accesses in developing countries 29 , 30 . These reports have in common the decrease in the waiting time for the procedures and the higher accessibility of patients to treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In India 38 almost all renal biopsies are done by nephrologists, either real time, US guided, or with previous localization and temporary catheter insertion with progressive use of US-guided technique in centers with enough economic resources. Also, tunneled hemodialysis catheters with US guidance and fluoroscopy, being PD catheters an infrequent technique due to financial and governmental constraints.…”
Section: Discussionmentioning
confidence: 99%